Utilization of Moringa Leaves to Overcome Chronic Energy Deficiency in Pregnant Women at Haruman Village, Leles District, Garut Regency in 2023 - Ramadani, Uswah Zayidah; Rukmaini; Inayah, Halida; Suwarni, Rini; Elisa; Rofyati, Noli; Mariana, Siska; Gunawan, Rina; Halimatussayidah (International Journal of Community Services, 2023)
Background: Community midwifery management was to improve the health of mothers and children, toddlers in the family so that healthy and prosperous families are realized in certain communities. In December 2022 Haruman Village has a good health status coverage, K1, K4, Linakes, KF3, KN3, and detection of risk maternity mother was 24%, pregnant women risk was 26%, but in April 2023 there is an increase in detection of women at risk which was 37.5%. Objective: Describe the priority of problems to interventions related to MCH / KB, together with the community through Community Service activities. Method: The data used secondary data from Haruman Village. The method of prioritizing problems uses the Delbeque method through Focus Discussion Group (FGD).  Results:  It was found that about 30 out of 80 pregnant women had a high risk or about 37.5% of them were mild anemia 12.5%, CED 18.75%, and age over 35 years 6.25% Therefore, the group intervened in the form of counseling on CED for pregnant women, which was carried out on Tuesday, May 23, 2023 at TPMB Rini Suwarni, the midwife of Haruman Village, and the provision of Moringa leaf pudding nutrition which can help improve nutrition in pregnant women with CEDs. Result: Counseling with the lecture method can increase knowledge about nutrition during pregnancy in preventing and overcoming CED. Empowering midwives and cadres to overcome CEDs can provide additional food in the form of processed moringa leaves. Conclusion: This community service program expected to be followed up elsewhere in the following year to support complementary innovations in preventing and treating CED in pregnant women